STRATEGI INOVATIF MANAJEMEN STRATEGIK SEKOLAH ISLAM MENGHADAPI DISRUPSI DIGITAL: ANTISIPASI, ADAPTASI, DAN AKSELERASI - Musthofa, Zackyl (As-Sulthan Journal of Education, 2025)
Digital disruption has changed the learning patterns, governance, and competence of educators. Islamic schools need to maintain Islamic values while increasing competitiveness through digital transformation. This study analyzes innovative management strategies at Madrasah Ibtidaiyah (MI) Miftahul Ulum Gresik, with the aim of describing anticipation, adaptation, and acceleration practices, identifying key success factors, and formulating a conceptual model that is applicable to Islamic schools. The research uses a qualitative approach with an intrinsic case study design. Data were collected through in-depth interviews, participatory observations, and document analysis, then analyzed using Braun–Clarke thematic analysis and Lincoln–Guba trustworthiness test. The results show that the anticipation phase is carried out through environmental scanning, digital needs mapping, and the preparation of a triennial roadmap. The adaptation phase includes digital media use policies, peer-mentoring-based multi-level training, gradual infrastructure improvements, and the integration of digital curriculum based on Islamic values. The acceleration phase can be seen in the implementation of digital learning, partnerships with local digital ecosystems, strengthening digital leadership, and developing a culture of innovation. These findings resulted in a SIF-ISD model that emphasizes that the digital transformation of madrasas relies on the orchestration of anticipative intelligence, adaptive capabilities, and accelerative innovation to support the sustainability of Islamic schools in the digital era.